Project management strategy for solving critical major delays in high rise building projects - Kyi Hlaing Win; Hadikusumo, Bonaventura H. W.; Chotchai Charoenngam; Santoso, Djoen San (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
This paper presents the weakness of project management strategy that could lead to financial loss and less trust of the public. It shares knowledge on project management and planning of activities and resource management. It also highlights the causes of the delay of a housing project in Myanmar, Dagon Seikkan as a case study. The purpose of the case study is to assess the efficiency, effectiveness, relevance, sustainability, and effects of the housing development project. The findings reveal that the housing project was not efficient, effective, relevant, or sustainable. A number of reasons of these delays are attributed to the inadequacy in the proper planning of work schedules and budget, lack of experience of the project management team and limited experienced in professional and leadership skill, procurement and usage of materials to ensure successful project completion. Some mitigating measures were taken within reasonable time frame but they could not compromise the delays of construction and not make the buildings{u2019} better quality. In construction projects, the project management strategy in each stage such as feasibility study, pre - construction, construction, commissioning, handover and project close out stage are all important process to attain the successful achievement.
A project submitted in partial fulfillment of the requirements for the degree of Master of Engineering (Professional) in Construction, Engineering and Infrastructure Management
Project (M.Eng.) - Asian Institute of Technology, 2016
Keywords: Project Management -- Planning -- Myanmar; Scheduling (Management); High-rise Apartment Buildings -- Myanmar -- Management